Coevolution of the tumor microenvironment revealed by quantum dot-based multiplexed imaging of hepatocellular carcinoma. (July 2013) - Fang, Min; Peng, Chun-Wei; Yuan, Jing-Ping; Zhang, Zhi-Ling; Pang, Dai-Wen; Li, Yan
Aim: This study aimed to provide new insights into the mechanisms of hepatocellular carcinoma (HCC) invasion by simultaneously imaging tumor cells and major components of the tumor microenvironment.Materials & methods: Formalin-fixed paraffin-embedded human HCC tissues were studied by conventional immunohistochemistry and quantum dot-based multiplexed imaging to reveal type IV collagen, LOX and tumor angiogenesis.Results: Type IV collagen degradation and repatterning in the extracellular matrix (ECM) was a continuous process, making the ECM harder, although more fragile and less resistant to cancer invasion. The distribution of LOX among cancer nests was heterogeneous, with higher expression in small cancer nests and lower expression in large cancer nests. LOX expression in cancer cells was associated with rigid stroma and tumor angiogenesis. Tumor angiogenesis occurred with type IV collagen presence. At the cancer invasion front, the ECM was hydrolyzed, with the prominent linear reorientation of type IV collagen surrounding cancer nests adjacent to neovessels.Conclusion: The visualization of the temporal–spatial relationship between type IV collagen, LOX and tumor angiogenesis revealed the coevolution process of HCC cells and their microenvironment, emphasizing an active role of the ECM during cancer invasion.